Development and Validation of UPLC-MS/MS Analysis for Sphingolipids Isolated from Velvet Antlers of Cervus elaphus - Khong, Quan T.; Han, Sung-Tai; Park, Inwha; Na, Minkyun (ACS Publications, 2024)
Deer velvet antlers, known as tonics, have created a large market as dietary supplements and have been consumed worldwide. Despite the high consumption of velvet antlers as dietary supplements, analytical methods for their identification and standardization remain limited. Quantitative analysis for gangliosides, considered quality indexes for velvet antlers, was developed to indirectly analyze the sialic acid obtained from chemical degradation. Owing to the complex and time-consuming chemical derivatization of gangliosides, a simple and rapid quality evaluation method for velvet antlers must be developed. For the first time, this study reports the isolation and structural elucidation of two new sphingomyelins (1 and 2), two known sphingomyelins (3 and 4), and four ceramides (5-8) as chemical markers from the velvet antlers of Cervus elaphus. To expedite and simplify the quality control of velvet antlers, advanced quantitative analysis of sphingolipids has been developed using ultra-performance liquid chromatography-mass spectroscopy.